A palearctic bark beetle, Crypturgus hispidulus Thomson (Coleoptera: Curculionidae: Scolytinae), new to North America discovered in New England, U.S.A. - Digirolomo, Marc F.; Sevigny, Joseph L. (Zootaxa, 2023)
Specimens of a bark beetle, Crypturgus hispidulus Thomson, 1870, were discovered in New England, U.S.A. This is the first record of this species established in North America. Misidentified specimen records were found from multiple states in different years, confirming establishment of the species in the Northeastern United States. The morphology is presented and a modified key to Crypturgus in North America is provided to facilitate species identification.